SMOKELESS TOBACCO CONTROL IN PAKISTAN - Ahmad, Fayaz; Javaid, Arshad; Khan, Zohaib (Journal of Postgraduate Medical Institute, 2021)
Smokeless tobacco denotes tobacco-containing products that are consumed without combustion by different methods like inhaling through the nose, sucking, or chewing. It has been estimated that there are 17 million smokeless tobacco users in Pakistan and the most frequently used forms of smokeless tobacco are Paan, Naswar, and Gutka. Naswar accounts for 60% of the total tobacco consumed in Peshawar, the capital city of Khyber Pakhtunkhwa. The levels of carcinogenic tobacco-specific nitrosamines in Naswar are higher than several smokeless tobacco products in the world. Evidence indicates that both globally and in Pakistan, smokeless tobacco control has almost always remained a neglected area compared to smoking control. The authors recently conducted a mixed-methods research study on smokeless tobacco control in Pakistan (STOP), focusing on Naswar and its supply chain in the Khyber Pakhtunkwa province of Pakistan. In this study, discussions with 38 points of sale and exclusive Naswar vendors, it was found that there was a clear agreement among the participants to support a ban on the sale of Naswar to minors, and similarly, they opposed illicit trade of these products. The participants partially agreed on the content disclosure of Naswar, its advertisement, and promotion. Mass media campaigns, group educations, and the use of special brochures or posters are recommended for the improvement of awareness and compliance among vendors.